Identification of cattle carrying alleles associated with resistance and susceptibility to the Bovine Leukemia Virus progression by real-time PCR - Forletti, Agustina (2013)
Abstract Previous studies have shown a significant association between polymorphisms of the BoLA DRB3 gene and Bovine Leukemia Virus (BLV) infection profile. The presence of allele ∗1501 has been associated with high proviral load in peripheral blood while allele ∗0902 has been associated with low proviral load. The purpose of this study was to develop allele-specific real-time PCRs to identify cattle carrying alleles associated with resistance (BoLA DRB3∗0902) or susceptibility (BoLA DRB3∗1501) to the BLV progression. Specific primers were designed and differential amplification was carried out by real-time PCR and monitored by SYBR® Green dye in DNA samples from peripheral blood. Conditions were also adjusted for traditional PCR amplification (end point amplification). These methods are rapid, simple and suitable for high throughput screening, and could aid in marker-assisted selection of BLV-resistant and susceptible cattle.